2017
DOI: 10.1016/j.pediatrneurol.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Somatic GNAQ Mutation is Enriched in Brain Endothelial Cells in Sturge–Weber Syndrome

Abstract: Background Sturge-Weber syndrome (SWS) is a rare congenital neurocutaneous disorder characterized by facial and extracraniofacial capillary malformations and capillary-venule malformations in the leptomeninges. A somatic mosaic mutation in GNAQ (c.548G>A; p.R183Q) was found in SWS brain and skin capillary malformations. Our laboratory showed endothelial cells (ECs) in skin capillary malformations are enriched for the GNAQ mutation. The purpose of this study is to determine whether the GNAQ mutation is also enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 24 publications
2
61
0
Order By: Relevance
“…It has since been shown that the activating R183Q mutation is enriched in endothelial cells of CM and SWS lesions. 8,9 Different somatic mutations in GNAQ and its homologue GNA11 have been reported in congenital hemangiomas. 10 In contrast, to our knowledge, no somatic variants have been definitely associated with infantile hemangioma.…”
mentioning
confidence: 99%
“…It has since been shown that the activating R183Q mutation is enriched in endothelial cells of CM and SWS lesions. 8,9 Different somatic mutations in GNAQ and its homologue GNA11 have been reported in congenital hemangiomas. 10 In contrast, to our knowledge, no somatic variants have been definitely associated with infantile hemangioma.…”
mentioning
confidence: 99%
“…In the ocular, cerebral and facial territories reproducibly affected by Sturge-Weber and cerebrofacial arteriovenous metameric vascular malformation syndromes, there are often malformations of adjacent nerves and NC-derived bones (Krings et al, 2007;Nakashima et al, 2014). Quail-chick xenografts have shown that endothelial cells can differentiate inappropriately in response to signals that are specific to these distinct sectors of NC-derived perivascular or SCP cells (Othman-Hassan et al, 2001); recently, causal somatic mutations in an intracellular signalling effector have been found within endothelial cells of those facial areas affected in Sturge-Weber syndrome (Huang et al, 2017). This implies that there remains a large class of human neurocristopathies to be identified as such, which are not only due to direct or indirect impairment of cell-autonomous NC differentiation, but also to their non-cellautonomous inductive functions.…”
Section: Many Birth Defects Are Imputable To Neural Crest Pathologymentioning
confidence: 99%
“…[25] Extensive dermal melanocytosis and phakomatosis pigmentovascularis are associated with mutations in GNAQ as well as in GNA11 (which does not have known somatic mutations in patients with SWS). [30] The mutations were detected at very low levels in affected tissues but were undetectable in the blood, indicating that these conditions are post-zygotic mosaic disorders. [28] A more strongly activating mutation in 209L of GNAQ is associated with uveal melanoma.…”
Section: Port-wine Birthmarks and Skin Manifestations In Swsmentioning
confidence: 99%